The Role of Additional Invasive Methods for Functional Verifications Shows to Repeat Revascularization in Patients with Coronary Artery Disease with Recurrent Angina after Coronary Artery Bypass Surgery - S. M. Fanta; E. V. Aksenov; V. V. Lazorishinetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
The data of 250 patients having coronary bypass surgery in our institution in the period from 2005 to 2014 was studied. The selected group of patients needed reintervention because of the recurrence of angina. The data of coronary ventriculografy and shunt angiography were analyzed. Efficacy of treatment by surgical and endovascular methods, optimized medical therapy was reviewed.